Assessing the Influence of Computational Thinking Technique on STEM Based and Non-STEM Based Subjects in Sarawak Schools - Shaadah, Shariman; Faizah, Mas'ud; Seleviawati, Tarmizi; Kartinah, Zen; Eaqerzilla, Phang (UNIMAS Publisher, 2024)
Computational thinking (CT) has gained prominence as an essential skillset in the digital age. This study investigates the influence of integrating CT techniques into both STEM and non-STEM subjects in schools across Sarawak, Malaysia. A mixed methods approach combined surveys of 426 students and 79 teachers with interviews of 5 teachers and 8 students. Results indicate CT integration enhanced problem-solving skills, logical reasoning, and critical thinking. Over 50% of teachers reported improved student performance in STEM and non-STEM subjects with CT techniques. Interviews highlighted benefits like increased engagement, but also challenges faced regarding teacher training, resources, and curriculum integration. Recommendations include focused teacher professional development, ensuring equitable access to technology, tailored curriculum approaches, and cultural sensitivity. This study provides insights into the multifaceted impacts of CT integration in the Sarawak education context. The blended findings underscore the potential of CT to develop relevant 21st century skills, but also highlight the need for systemic support for effective implementation. This research contributes to strategic efforts to nurture computational literacy and harness the power of CT across all subject areas within the region's schools.